Veterinary Preventive Medicine - Kustritz, Margaret Root (Open textbook library., 2022)
Goals of preventive medicine are to protect, promote, and maintain health and well-being and to prevent disease, disability, and death. Veterinary preventive medicine is an important component of veterinary training not only to ensure animal health but also to help veterinary students learn necessary information and skills for participation in global animal and human health challenges and disease prevention.